Curriculum Evaluation of the Implementation of Sekolah Penggerak Program at TK Abaabil Bila Sidrap - Riskal Fitri (Edumaspul: Jurnal Pendidikan, 2022)
The aims of this study are 1) to find out whether TK Abaabil Bila has made Kepmendikbud Number 1177/M/2020 concerning the Sekolah penggerak Program and Kepmendikbud RI Number 958/P/2020 concerning Learning Outcomes in Early Childhood Education, Basic Education, and Middle Educationah as a reference for curriculum development; 2) To find out the availability of Human Resources and Infrastructure in supporting the implementation of the PSP curriculum at TK Abaabil Bila Sidrap; 3) To find out the implementation of the Sekolah penggerak Program curriculum at TK Abaabil Bila Sidrap; 4) To find out the results of the implementation of the Sekolah penggerak Program curriculum at TK Abaabil Bila Sidrap. Qualitative research is designed in the form of case study research involving all stakeholders in TK Abaabil Bila Sidrap. Data collection techniques use observation sheets, interviews and documentation. While the data analysis technique used is descriptive statistics. The results of the research using Context, Input, Process and Product (CIPP) are seen from the aspects of Context, Input, Process and Product that the implementation of the sekolah penggerak curriculum is in accordance with the learning objectives. The implementation of this curriculum innovation is expected to have an impact on the standard quality of the level of achievement of child development, the quality of learning outcomes, the quality of teachers, the acceleration of school digitization and the profile of Pancasila students.